On the trail - Thorpe, Kiki (Thorpe, Kiki. Never girls, 2015)
"Four best friends--Kate, Mia, Lainey, and Gabby--travel to Never Land, where they find adventure, friendship, and mystery! When the girls realize that animal talent fairy Fawn is missing, the search is on"--